Três Ensaios Sobre Mercado de Trabalho e Crime - Freire Júnior, José (2018)
This thesis is formed by the combination of three studies in the area of labor market and crime, seeking to raise questions about the motivation of economic crimes committed by workers within their work environment, and the most effective forms of punishment. In the first two chapters two different methodologies were used, but with the same objective, to punish workers who commit fraud, and in the third chapter a review on the main theories that try to explain the motivations of the frauds that happen in the private organizations. The first chapter, Economic Crimes in Private Companies: A Bibliographical Review, seeks to rescue the main theories developed by researchers about fraud committed by internal members of private organizations and try to understand the motivation that lead some people to commit fraud where they work. In addition, to present studies carried out by international consultants on fraud in Brazil, seeking to draw a profile of the fraudster and the attitudes taken by private organizations when frauds occur. The second chapter, A Model of Matching in Punishment Against Economic Crimes Committed in Private Companies, sought to find ways of punishment that inhibit the practice of robberies in private companies. Using a matching model and defining a function called a worker's loss function, we obtained the unemployment rate, reserve wage, Market Tightness and the value of the crime. The results show that financial deviations occurring in companies affect the reserve wage and the marginal productivity of labor, and that only with cumulative penalties such as imprisonment, seizure of deferred resources and fines does satisfactory results in terms of punishment. The third and final chapter, A Model of Static and Dynamic Games in Punishment Against Economic Crimes Committed in Private Enterprises, still within the context of the labor market and crime, treats as premise the fact that more efficient internal controls and speedy justice are important mechanisms in the fight to fraud within organizations. Applying a game theory model and dividing it into two states of nature, we obtain the Nash equilibria for the two states, in which for the first state of nature we have the participation of the firm and the worker, and in the second state of nature, the firm, the employee and the government, represented in the figure of the public prosecutor and the judiciary who are representatives of society. The results indicate that with swift justice, efficient audits and punishments applied cumulatively, in addition to a high moral cost to the offender, there could be drastic reductions in the desire and opportunity for the practice of fraud crimes by workers within private companies.